The use of Talking Chips Technique in Cooperative Learning Models to Increase Language Ability for Visual Impairment Students - Tiastiningrum Nugrahanti; Budi Santoso; Marja Marja (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2021)
This research aims to gain information from various written sources related to the cooperative learning model of talking chips types in improving the oral language skills of students with visual impairments. This research was conducted using a content analysis-based literature review, involving 25 articles and 12 books. The research data used is in the form of secondary data taken from printed books, a collection of journals, previous researches, and relevant websites. The results of the literature review show: (1) cooperative learning model of talking chips types can improve oral language skills in composing simple sentences of students with visual impairments; (2) there are differences in the oral language skills between students with visual impairments low vision and blind; (3) the use of cooperative learning model of talking chips types becomes an innovation in the learning process of students with visual impairments. The results of this research implied that the cooperative learning model of talking chips types could serve as an alternative to improve the oral language skills of students with visual impairments.